(untitled) (Global Journal of Management and Business Research, 2016)
This paper aims to implement a new test for the integrated model by using the theory of the probability tree diagram. This test is implemented because it gives more accurate results compared with the previous test that was implemented to test the integrated model by using the simple random sampling (SRS) probability theory. So this paper will provide more accurate results, which will increase the confidence of systems builders in the integrated model.